The conflict of characters in novel Sumbang by Musa Ismail (a study of Literary Psychology) and its implications for learning in schools - Mulziani (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2023)
This article describes the conflict of characters in the novel Sumbang by Musa Ismail and its implications in learning in schools This type of research is qualitative research using descriptive methods of analysis. The purpose of this study is to describe the author's views on the social conflicts that occur in the novel Sumbang and its implications for learning in schools. The data collection techniques used are documentation, interview, record and record techniques. The source of this research data is a novel with the title Sumbang and the subject of the informant, namely Mr. Musa Ismail as the author of the novel Sumbang. The results showed that there is an author's view of character conflicts, namely, character conflicts between individuals and individuals and individuals with society or groups.